Yoga and Sports Performance: A Qualitative Analysis of Its Psychological Benefits - Mr. Swapnil Bhaip; Dr. Yashodhan Kharade (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Yoga is well known as a useful method for improving both physical and mental health. In the field of sports, psychological resilience, focus, and emotional stability play a important part in achieving peak performance. This study explores the psychological benefits of yoga and its impact on sports performance through a qualitative analysis. The research aims to understand how yoga influences mental toughness, concentration, stress management, and overall psychological well-being among athletes. By employing a detailed study, data was collected through in-depth interviews and focus group discussions with athletes across different sports disciplines. The study utilized thematic analysis to interpret the responses and identify key psychological benefits derived from yoga. Findings suggest that yoga fosters emotional stability, reduces anxiety, and enhances athletes’ focus, contributing to improved performance in competitive sports. Participants reported increased self-awareness, better stress regulation, and enhanced confidence after adding yoga into their training plans. These results emphasize the importance of integrating yoga into players training programs to optimize mental preparedness and overall performance.